2017
DOI: 10.1007/s12079-017-0386-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of ubiquitin-conjugating enzyme Ube2j1 phosphorylation and its degradation by proteasome during endoplasmic stress recovery

Abstract: The human Ube2j1 and Ube2j2 are the only ubiquitin-conjugating enzymes (E2s) that are localized to endoplasmic reticulum (ER) through its C-terminal transmembrane domains. Ube2j1 is a known substrate of MAPK signalling pathway and it is phosphorylated at serine-184 during ER stress. Here, we demonstrate that Ube2j1, not Ube2j2 is essential for the recovery of cells from transient ER stress. The ectopic expression of wild-type Ube2j1 and phospho-mimic mutant, Ube2j1 S184D but not phospho-mutant Ube2j1 S184A can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…The ER is responsible for protein proofing and ensuring that all initiated proteins are correctly folded before secretion out of the cell. Misfolded proteins are subject to re‐folding until they are successfully folded, whereas terminally misfolded proteins are retro‐translocated into the cytosol for ER‐associated degradation (ERAD) either via the ubiquitin‐proteasome system or are degraded in a ubiquitin independent manner 15–17 . The ER contains numerous chaperones that assist the protein folding process, including HSP60, calnexin, calreticulin and glucose‐regulated protein (GRP)78 15 .…”
Section: Endoplasmic Reticulum (Er) Stressmentioning
confidence: 99%
“…The ER is responsible for protein proofing and ensuring that all initiated proteins are correctly folded before secretion out of the cell. Misfolded proteins are subject to re‐folding until they are successfully folded, whereas terminally misfolded proteins are retro‐translocated into the cytosol for ER‐associated degradation (ERAD) either via the ubiquitin‐proteasome system or are degraded in a ubiquitin independent manner 15–17 . The ER contains numerous chaperones that assist the protein folding process, including HSP60, calnexin, calreticulin and glucose‐regulated protein (GRP)78 15 .…”
Section: Endoplasmic Reticulum (Er) Stressmentioning
confidence: 99%
“…UBC6e can be phosphorylated on S184. This phosphorylation occurs both during ER stress and upon inhibition of protein synthesis 14 . Based on the epitope identified for VHH05, the site of phosphorylation (S184) maps very close to, if not within the binding site of VHH05.…”
Section: Vhh05 Binding Is Independent Of Phosphorylation Of Ubc6ementioning
confidence: 99%
“…ER stress occurs in various cardiovascular diseases with impaired proteostasis (Ochoa et al, 2018). A study from 2017 identified ubiquitin-conjugating enzyme E2 J1 (UBE2J1) phosphorylation at serine 184 as being important for recovery of ER stress to maintain proteostasis (Elangovan et al, 2017). It was reported that UBE2J1 is phosphorylated at serine 184 by mitogen kinase 2 (MK2) as a mechanism to alleviate ER stress (Menon et al, 2013).…”
Section: Phosphorylations That Regulate Ubiquitination Enzymesmentioning
confidence: 99%
“…It was reported that UBE2J1 is phosphorylated at serine 184 by mitogen kinase 2 (MK2) as a mechanism to alleviate ER stress (Menon et al, 2013). Phosphorylated UBE2J1 has higher affinity for the E3 ligase, c-IAP1, and that cells expressing a phosphonull UBE2J1 cannot recover from ER stress (Elangovan et al, 2017). The authors also reported that phosphorylated UBE2J1 is degraded by the proteasome, potentially as a feedback loop (Elangovan et al, 2017).…”
Section: Phosphorylations That Regulate Ubiquitination Enzymesmentioning
confidence: 99%